Association of Tree Species in Bagale Forest Reserve, Adamawa State, Nigeria - Omijeh , J. E.; Tella , I. O. (Advanced Research in Biological Science Vol. 3, 2023)
This chapter highlights the degree of species association among the indigenous trees of this reserve after ascertaining whether there is association. Bagale forest reserve is a valuable ecological resource constituted in December, 1954. Over the years, this ecosystem has been vulnerable to various forms of anthropogenic activities which no doubt had deleterious effects on the forest structure and species composition. The relationship among indigenous trees \(\ge\) 10cm girth at diameter at breast (dbh) height was assessed to determine their level of association in the Bagale Forest Reserve, Adamawa State, Nigeria. Fifteen sample plots each measuring 100m x 100m were laid in five fragments, at Tudun Wada (<200m) Holin (200 - 300m), Modire (300 - 400m) Lugga (400 - 500m) and Wurodole (>500m) above sea level. Trees in each quadrat were identified and inventoried and association among them subjected to statistical analysis using Pearson's correlation coefficient. The survey yielded 312 individual trees which were grouped into 45 tree species with positive and negative relationships (association). Results showed that positive and negative correlations at (p=0.1) and (p=0.5) were obtained among these trees in the study area. The result also revealed that the same tree species wih different sizes led to different herbaceous species, richness, diversiy and composition under and around the trees crowns. It is advised that studies of the synecology of forest reserves be conducted throughout the nation to help with the study of trees' distribution patterns because the information gathered from such an endeavour will be useful for planning, managing, and forming policy related to forests.